2022
DOI: 10.1002/bse.2973
|View full text |Cite
|
Sign up to set email alerts
|

Bank green lending and credit risk: an empirical analysis of China's Green Credit Policy

Abstract: This study empirically investigates the relationship between banks' green lending and their credit risk, and how Chinese green finance regulations contribute to the solvency of individual banks and the resilience of the financial system. Analysing a sample of 41 Chinese banks from 2007 to 2018, we find that the association between a bank's (relative) green lending as a proportion of its overall loan portfolio, and its credit risk, depends critically on the size and structure of state ownership. While the imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 76 publications
3
33
0
Order By: Relevance
“…Moreover, implementing green credit can discourage bank executives from excessive risk-taking behaviours in pursuit of high profts, which increases nonperforming loan rates. Te shift from a shareholder-centric to a stakeholder-centric governance model balances the interests of the bank's investment and noninvestment stakeholders, thereby curbing excessive risktaking behaviours by management and protecting bank value [4]. From the customer perspective, green credit can achieve higher customer loyalty and curb bank risk [37].…”
Section: Hypothesis 2 Green Credit Policies Improve Commercial Banks'...mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, implementing green credit can discourage bank executives from excessive risk-taking behaviours in pursuit of high profts, which increases nonperforming loan rates. Te shift from a shareholder-centric to a stakeholder-centric governance model balances the interests of the bank's investment and noninvestment stakeholders, thereby curbing excessive risktaking behaviours by management and protecting bank value [4]. From the customer perspective, green credit can achieve higher customer loyalty and curb bank risk [37].…”
Section: Hypothesis 2 Green Credit Policies Improve Commercial Banks'...mentioning
confidence: 99%
“…Some banks' lack of environmental risk management may lead to green loan losses. For instance, Zhou et al [4] found a nonsignifcant association between bank green lending and risk performance across the banking sector as a whole. Compared to their large peers, city/regional-level commercial banks have more limited capacity and industry expertise and less developed risk management systems, all of which may contribute to the economic losses they experience in green lending [39].…”
Section: Hypothesis 2 Green Credit Policies Improve Commercial Banks'...mentioning
confidence: 99%
See 3 more Smart Citations